Carbapenem-Sparing Strategies for ESBL Producers: When and How - Ilias Karaiskos; Helen Giamarellou (MDPI AG, 2020)
Extended spectrum β-lactamase (ESBL)-producing bacteria are prevalent worldwide and correlated with hospital infections, but they have been evolving as an increasing cause of community acquired infections. The spread of ESBL constitutes a major threat for public health, and infections with ESBL-producing organisms have been associated with poor outcomes. Established therapeutic options for severe infections caused by ESBL-producing organisms are considered the carbapenems. However, under the pressure of carbapenem overuse and the emergence of resistance, carbapenem-sparing strategies have been implemented. The administration of carbapenem-sparing antibiotics for the treatment of ESBL infections has yielded conflicting results. Herein, the current available knowledge regarding carbapenem-sparing strategies for ESBL producers is reviewed, and the optimal conditions for the “when and how” of carbapenem-sparing agents is discussed. An important point of the review focuses on piperacillin−tazobactam as the agent arousing the most debate. The most available data regarding non-carbapenem β-lactams (i.e., ceftolozane−tazobactam, ceftazidime−avibactam, temocillin, cephamycins and cefepime) are also thoroughly presented as well as non β-lactams (i.e., aminoglycosides, quinolones, tigecycline, eravacycline and fosfomycin).